Current CT and MRI possibilities to diagnose and differentiate dementia - Kurys-Denis, Ewa; Papuć, Ewa; Krupski, Witold; Stelmasiak, Zbigniew (Current Problems of Psychiatry, 2011)
All of the major neurodegenerative disorders have relatively specific imaging findings that can be identified. New MRI imaging techniques carry the hope of revolutionizing the diagnosis of neurodegenerative disease so as to obtain a complete molecular, structural, and metabolic characterization, which could be used to improve diagnosis and to stage each patient and follow disease progression and response to treatment. In this review we provide an overview of the various structural computed tomography (CT) and magnetic resonance imaging (MRI) methods used to image neurodegenerative disease and discuss their usefulness in specific neurodegenerative disorders.